Space-limited domain annealing of CuI thin films for highly responsive ZnO nanorods based ultraviolet photodetectors. (1st November 2021) - Tan, Bo; Luo, Guangcan; Zhang, Ziling; Jiang, Jing; Guo, Xuxiang; Li, Wei; Zhang, Jingquan; Wang, Wenwu
Abstract: Ultraviolet (UV) photodetectors with high responsivity, fast response speed and better stability have attracted much attention. In this work, heterojunctions based on ZnO nanorods (ZnO NRs)/CuI were successfully prepared by combinational chemical hydrothermal and drop-coating methods, which could be employed as self-powered and external powered UV photodetectors. The ZnO NRs were homogeneous covered and coated by CuI layer. The introduction of CuI enhanced the UV emission and weakened the defect emission of ZnO. The space-limited domain annealing was adopted to post-treat the CuI layer, which is useful to prevent the significant loss of iodine in the thin films. The UV photodetector based on ZnO NRs/CuI shows the responsivities of 86.84 mA W −1 at 0 V bias voltage and 4.41 × 10 4 mA W −1 at −2.5 V bias voltage under 380 nm irradiation. The rise and decay time for the devices are both 110 ms. The incorporation of CuI benefits the separation of photon-generated carriers. The facile, practical and low-cost synthesis makes ZnO NRs/CuI heterojunction a potential candidate for vertical UV-A photodetectors with high responsivity. Highlights: The ZnO NRs/CuI heterojunction was fabricated by the facile, low-temperature, and low-cost methods. Space-limited domain annealing was used to reduce the significant loss of iodine in the thermal treated process of CuI. Self-powered ZnO/CuI heterojunction exhibits a responsivity of 86.84 mA/W under 380 nm irradiation. External powered ZnO/CuI heterojunction exhibits a responsivity of 4.41×104 mA/W at -2.5 V bias under 380 nm irradiation.